Pengaruh Kecanduan Bermain Gadget dan Kontrol Orang Tua Terhadap Prestasi Belajar Kognitif Peserta Didik Kelas V SD Negeri Kubangpari 02 - Sholihah Sholihah; Laelia Nurpratiwiningsih; Muamar Muamar (Jurnal Ilmiah Wahana Pendidikan, 2022)
Abstract This research aims to determine whether there is an effect between addiction to playing gadgets on cognitive learning achievement, the influence between parental control on cognitive learning achievement, and the effect of addiction to playing gadgets and parental control simultaneously or simultaneously on cognitive learning achievement. The method in this research is correlational quantitative. The sampling technique in this research is in the form of total sampling. The sample in this research were all fifth grade students of SD N Kubangpari 02, totaling 53 students. The results obtained are (1) There is no effect of the gadget addiction variable (X1) on cognitive learning achievement (Y), which is proved by the t-test results with a significant value of 0.446> 0.05. (2) There is an effect of parental control variable (X2) on cognitive learning achievement (Y), which is proved by the t-test result with a significant value of 0.009 <0.05. (3) There is a simultaneous effect of addiction to playing gadgets and parental control on cognitive learning achievement of fifth graders at SD Negeri Kubangpari 02, which is proved by the f-test results with a significant value of 0.022<0.05.